КОМПЬЮТЕР ГРАФИКАСИНИ ЎҚИТИШДА EMBARCADERO ДАСТУРЛАШ ТИЛИДАН ФОЙДАЛАНИБ 3D ГРАФИК ОБЪЕКТЛАР ЯРАТИШ - Алламбергенова, М.Х.; Мадаминов, У. (SCIENCE and SOCIETY, 2019)
The article discusses the advantages of computer graphics, including the programming of three-dimensional graphics. Today, there are many 3D computer programs. One of them is the Embarcadero program. This program makes it possible, with the help of the programming language, to create object models and three-dimensional graphics.